Gọi tổng này là A . Ta có :
A = 3 + 32 + 33 + ... + 39
A = ( 3 + 32 + 33 ) + ( 34 + 35 + 36 ) + ( 37 + 38 + 39 )
A = 3 . ( 1 + 3 + 32 ) + 34 . ( 1 + 3 + 32 ) + 37 . ( 1 + 3 + 32 )
A = 3 . 13 + 34 . 13 + 37 . 13
A = 13 . ( 3 + 34 + 37 )
Vì A có thừa số 13 nên A \(⋮\)13
gọi tổng này là A
ta có : A=3+3\(^2\)+3\(^3\)+...+3\(^9\)
A=(3+3\(^2\)+3\(^3\))+(3\(^4\)+3\(^5\)+3\(^6\))+(3\(^7\)+3\(^8\)+3\(^9\))
A=3.(1+3+3\(^2\))+3\(^4\).(1+3+3\(^2\))+3\(^7\).(1+3+3\(^2\))
A=3.13+3\(^4\).13+3\(^7\).13
A=13.(3+3\(^4\)+3\(^7\))
vì A có thừa số 13 nên A\(⋮\)13